Examining the impact of video-based outpatient education on patient demand for a rheumatology CNS service. (14th October 2021) - Murphy, Louise; Moore, Stephen; Swan, Joan; Hehir, Davida; Ryan, John
Abstract : Background: Patient demand for education and access to the clinical nurse specialists (CNSs) during the rheumatology clinic at one hospital in Ireland was increasing. Alternative methods of providing patient education had to be examined. Aims: To explore the efficacy of video-based outpatient education, and its impact on demand for the CNSs. Methods: A video was produced to play in a rheumatology outpatient department. A representative sample of 240 patients (120 non-exposed and 120 exposed to the video) attending the clinic was selected to complete a questionnaire exploring the effect of the video. Data were analysed using chi-square tests with Yates' continuity correction. Findings: Demand for the CNSs was six times higher in the non-exposed group compared with the exposed group (non-exposed: 25%, exposed: 4.8%) (χ 2 =15.7, P =0.00007), representing a significant decrease in resource demand. Conclusion: High-quality educational videos on view in the rheumatology outpatient department provide patients with information sufficient to meet their educational needs, thus releasing CNS resources.